Moral values ​​in preserving the environment Buya Hamka and Quraish Shihab's Perspective (Comparative Study of Tafsir Al Azhar and Al Misbah) - Nugraha, Rasyid Tahta; Faza, Abrar Dawud (Academy of Education Journal, 2024)
This research is motivated by the increasingly complex environmental problems in Indonesia, such as deforestation, water and air pollution, ecosystem damage, and the significant impacts of climate change. The environmental crisis is not only caused by inappropriate policies, but also by the low public awareness of the importance of preserving nature. In this context, Islamic thought derived from the Qur'an is relevant to provide moral and practical solutions. This study examines the wisdom of two great Indonesian scholars, Buya Hamka and Quraish Shihab, through their tafsir works, Tafsir Al-Azhar and Tafsir Al-Misbah, which contain views on the relationship between humans and nature. This comparative study aims to identify the relevance of the interpretations of the two figures in answering contemporary environmental problems in Indonesia. Although there are differences in methodology in interpretation, both Buya Hamka and Quraish Shihab emphasize the importance of environmental ethics and human responsibility as caliphs on earth. In conclusion, their interpretations not only have theological value, but also provide relevant practical guidelines for addressing environmental challenges in Indonesia.